Faculty professional development in emergent pedagogies for instructional innovation in dental education. (10th December 2015) - Zheng, M.; Bender, D.; Nadershahi, N.
Abstract: Innovative pedagogies have significantly impacted health professions' education, dental education included. In this context, faculty, defined in this study as instructor in higher education, has been increasingly required to hone their instructional skills. The purpose of this exploratory study was to share the design, implementation and preliminary outcomes of two programmes to enhance dental faculty's instructional skills, the Teaching and Learning Seminar Series and the Course Director Orientation . Data sources included faculty and student surveys developed and administered by the researchers; data extracted from the learning management system; reports from the learning analytics tool; and classroom observations. Participants' satisfaction, self‐reported learning, instructional behavioural change, and impact on student learning behaviours and institutional practice were assessed borrowing from Kirkpatrick's 4‐level model of evaluation of professional development effectiveness. Initial findings showed that faculty in both programmes reported positive learning experiences. Participants reported that the programmes motivated them to improve instructional practice and improved their knowledge of instructional innovation. Some faculty reported implementation of new instructional strategies and tools, which helped create an active and interactive learning environment that was welcomed by their students. The study contributes to literature and best practice in health sciences faculty development in pedagogy and may guide other dental schools in designing professional development programmes.